Isolation and characterization of amyloid‐like protein aggregates from soya beans and the effect of low pH and heat treatment on their stability. Issue 10 (9th August 2022) - Jangir, Neelam; Bangrawa, Shreya; Yadav, Tamanna; Malik, Shweta; Alamri, Abdulhakeem S.; Galanakis, Charis M.; Singh, Manish; Yadav, Jay Kant
Abstract: Purified soya bean proteins (glycinin and conglycinin) are known to form amyloid‐like aggregates in vitro at a higher temperature. Soya beans (chunks) are textured proteinaceous vegetables made from defatted soya flour by heating it above 100°C and extruding under high pressure. Therefore, it was assumed that subjecting the soya bean proteins to high temperatures raises the possibility of forming amyloids or amyloid‐like protein aggregates. Hence, the present study aimed to examine the presence of amyloid‐like protein aggregates in soya beans. The isolated protein aggregates from hydrated soya beans displayed typical characteristics of amyloids, such as the red shift in the absorption maximum ( λ max ) of Congo red (CR), high Thioflavin T (ThT), and 8‐Anilinonapthalene‐1‐sulfonate (ANS) binding, and fibrilar morphology. Furthermore, these aggregates were found to be stable against proteolytic hydrolysis, confirming the specific property of amyloids. The presence of amyloid‐like structures in soya beans raises concerns about their implications for human nutrition and health. Practical applications: Protein aggregation has usually been considered detrimental. The traditional food‐processing conditions, such as thermal processing, are associated with protein denaturation and aggregation. The formation of ordered protein aggregates with extensive β‐sheet are progressively evident in various protein‐rich foods known as amyloid, which expands food safety concerns. Instead, it is also associated with poor nutritional characteristics. The present study concerns the presence of amyloid‐like protein aggregates in widely consumed native soya beans, which are manufactured by extensive heat treatment of defatted soy flour. Although there is no indication of their toxicity, these aggregates are found to be proteolytically resistant. The seminal findings in this manuscript suggest that it is time to adapt innovative food processing and supplementation of bioactive molecules that can prevent the formation of such protein aggregates and help maximize the utilization of protein‐based nutritional values. Abstract : During preparation of soy chunks, the proteins in it undergo severe structural changes leading to disruption of their native structures and exposure to aggregation‐prone regions. Such denatured proteins subsequently undergo structural changes to acquire beta‐sheet. Further, these sequences are released from a parent protein and promptly aggregate through beta‐sheet formation upon proteolytic digestions.